Effect of community based nutritional education on knowledge, attitude and compliance to IFA supplementation among pregnant women in rural areas of southwest Ethiopia: a quasi experimental study - Diriba Kumara Abdisa; Debela Dereje Jaleta; Dereje Tsegaye; Mohammedamin Hajure Jarso; Gemechis Dereje Jaleta; Gamachis Firdisa Tolesa; Keno Melkamu Kitila (BMC, 2023)
Abstract Background Compliance with the iron folic acid supplementation is low and not at the required level to prevent anaemia during pregnancy in many countries, including Ethiopia, even though an iron-folic acid supplementation program is being implemented. The aims of this study were to determine the effect of community-based nutritional education on knowledge, attitude, and compliance to IFA supplementation in Ilu Aba Bor zone of southwest Ethiopia. Method A pretest-posttest quasi-experimental study design consisting of intervention and control group was conducted among pregnant women. The total sample size of 472, therefore, 236 pregnant women for each interventional and control group from 16 kebeles were randomly selected in two districts. A multi-stage sampling technique was used to select the study participants. Then, individual study units were selected using a simple random sampling technique and followed until the end of the study period. Effect of community-based nutritional education on knowledge, attitude, and compliance to IFA supplementation among pregnant women in rural areas were measured. Results A total of 472 pregnant women participated in the study during the baseline and 437 (92.6%) were in the study until the end. The majority (49.2%) of respondents were 21-25 years of age, with a mean age of 23.4 (SD = 3.7) years. Community-based nutrition has resulted in a statistically significant increase in levels of maternal knowledge of IFAS by 15.2% in the intervention group compared to 5.1% in the control group. Similarly, the intervention group had odds of developing a positive attitude toward IFA 5.6 (4.01, 7.85) times higher than the control group. Moreover, in this study, the odds of compliance towards IFA supplementation were 3.9 (2.67, 5.57) times higher among those who received nutrition education than those women who did not. Conclusion This study revealed that community-based nutritional education can result in a significant change in knowledge, attitude, and compliance towards IFA supplementation and supports the literature suggesting the importance of the intervention to overcome the problem of poor compliance and its associated consequences.